First record of feather-loss disorder in Antarctic penguins - Barbosa, Andrés; Colominas Ciuró, Roger; Coria, Néstor Rubén; Centurión, Mara; Sandler, Rosana Veronica; Negri, Agustina; Santos, Mercedes (Antarctic Science)
Little is known about diseases affecting Antarctic wildlife (Kerry & Riddle 2009). Understanding the patterns, causes and effects of disease in these populations is crucial as many of these species are already threatened by rapid environmental changes brought about by climate change and increases in human activity. Although Antarctic penguins are one of the best studied organisms on the continent in terms of health, the published information is also scarce and fragmented (Barbosa & Palacios 2009). This paper reports for the first time, a new disease present in Antarctic penguins, the feather-loss disorder. The feather-loss disorder is characterized by premature loss of feathers resulting in exposed skin.In penguins, the disorder was first observed in African penguin (Spheniscus demersus (L)) chicks, both in captivity and the wild in 2006 and 2008, respectively, and in Magellanic penguins (S. magellanicus (Forster, 1781)) in 2007 (Kane et al. 2010). The cause is still uncertain but avian polyomavirus, the beak and feather disease virus or a bacterial pathogen have been proposed as potential agents Fil: Barbosa, Andrés. Consejo Superior de Investigaciones Científicas; España. Museo Nacional de Ciencias Naturales. Departamento de Ecología Evolutiva; España Fil: Colominas Ciuró, Roger. Consejo Superior de Investigaciones Científicas; España. Museo Nacional de Ciencias Naturales. Departamento de Ecología Evolutiva; España Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Centurión, Mara. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Sandler, Rosana Veronica. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Negri, Agustina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. ...